2023
DOI: 10.1113/ep091195
|View full text |Cite
|
Sign up to set email alerts
|

Lower systemic nitric oxide bioactivity, cerebral hypoperfusion and accelerated cognitive decline in formerly concussed retired rugby union players

Abstract: New Findings What is the central question of this study?What are the molecular, cerebrovascular and cognitive biomarkers of retired rugby union players with concussion history? What is the main finding and its importance?Retired rugby players compared with matched controls exhibited lower systemic nitric oxide bioavailability accompanied by lower middle cerebral artery velocity and mild cognitive impairment. Retired rugby players are more susceptible to accelerated cognitive decline. Abstract Following retir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…As would be expected with chronic exposure to contact events, Owens et al. ( 2023 ) found that the players with a previous history of at least one concussion had persistent neurological symptoms. These symptoms included headache, worsened memory, and feelings of anxiety.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…As would be expected with chronic exposure to contact events, Owens et al. ( 2023 ) found that the players with a previous history of at least one concussion had persistent neurological symptoms. These symptoms included headache, worsened memory, and feelings of anxiety.…”
mentioning
confidence: 82%
“…Overall, the authors found that retired rugby union players with a history of concussion were defined by the presence of lower systemic bioactive NO and persistent neurological symptoms, which were accompanied by cognitive impairment and cerebrovascular dysfunction at rest and in response to hyper-/hypocapnia. The current findings by Owens et al (2023) naturally lead to questions related to the impacts of acute concussion on this biomolecular-cerebrovascular-neurocognitive cascade and where interventions may occur to help improve long-term care in athletes exposed to repetitive contact activities. Indeed, data suggest that in the 7 days following a concussion in young athletes, dynamic changes in cerebral blood flow and microstructure seem to occur, though with a large degree of heterogeneity (Churchill et al, 2017).…”
mentioning
confidence: 90%
See 3 more Smart Citations